BUBBLE PROPERTY DI INDONESIA: ANALISIS EMPIRIS SURVEI HARGA PROPERTI RESIDENSIAL - Valerio Fanama; Rulyusa Pratikto (Jurnal Administrasi Bisnis, 2019)
Property is a sector that is very influential for Indonesia’s economy, so Bank Indonesia issued a Residential Property Price Survey to monitor property prices in big cities in Indonesia. The survey is done to monitor the condition of the property to prevent the occurrence of bubble conditions. This study aims to analyse the factors that are suspected to affect property prices in Indonesia, then compare the actual property price index with its fundamental property price index to determine the condition of property in Indonesia. As a result, Indonesia's GDP and inflation rate statistically affect the Indonesia’s House Price Index in all categories, while the amount of consumption credit only has a statistically significant effect on the Indonesia’s House Price Index of Small Houses, and the LTV ratio policy only has a statistically significant effect on the Indonesia’s House Price Index of Large Houses. Furthermore, Indonesia experienced bubble conditions in certain periods, but these conditions were considered harmless, because the bubble rate was not too large, and the bubble condition did not last for a long time.